1977
DOI: 10.1901/jaba.1977.10-465
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Control in the Classroom as a Function of the Behavior Reinforced

Abstract: Eight fifth-and sixth-grade children with behavior problems performed in a classroom under three conditions: (1) unreinforced baseline, (2) reinforcement for being on task, and (3) reinforcement for the accuracy and rate of math problems solved. The teacher was absent for a portion of the class session under each of these conditions. In the teacher's absence, on-task behavior declined markedly and disruption markedly increased, regardless of the reinforcement condition in operation. In addition, the teacher's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…Though students may have previously demonstrated mastery of a task or material, they may continue to rely on the presence of an adult or treatment contingency to remain engaged or to complete activities (Stahmer & Schreibman, 1992). The removal of close supervision, adult prompting, or contingencies may lead to reoccurrence of off-task behaviors, and to a decline in appropriate responding and productivity (Dunlap & Johnson, 1985;Marholin & Steinman, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Though students may have previously demonstrated mastery of a task or material, they may continue to rely on the presence of an adult or treatment contingency to remain engaged or to complete activities (Stahmer & Schreibman, 1992). The removal of close supervision, adult prompting, or contingencies may lead to reoccurrence of off-task behaviors, and to a decline in appropriate responding and productivity (Dunlap & Johnson, 1985;Marholin & Steinman, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigators have reported increases or decreases in the frequency of a target behavior (R) when the reinforcement frequency for some other behavior (re) changed in the opposite direction. For example, Ayllon, Layman, and Kandel (1975), Ayllon and Roberts (1974), Kirby andShields (1972), Marholin andSteinman (1977), and Winett and Roach (1973) found that the rate of disruptive behavior (R) decreased when reinforcement was arranged for academic behavior (re), just as Equation 3 requires. Similarly, Brawley, Harris, Allen, Fleming, and Peterson (1969) and Lovaas, Litrownik, and Mann (1971) found that the frequency of self-stimulatory behavior decreased when appropriate behavior was reinforced.…”
mentioning
confidence: 99%
“…In Figure 2, In one of the few previous experiments to examine independent responding (i.e., in a setting without any supervisor), Marholin and Steinman (1977) found that when a teacher left the dassroom, the performance of behavior-problem fifth and sixth graders declined dramatically. Those authors increased the amount of time spent working and the accuracy of work completed by providing reinforcement based on the products of responding during the teacher's absence.…”
Section: Discussionmentioning
confidence: 91%
“…In particular, training personnel or distinguishable treatment settings can come to occasion appropriate behavior because such stimuli may be regularly associated with reinforcement for these desirable responses (Koegel & Rincover, 1977). Conversely, the absence of such stimuli may serve analogous functions and signal a child to cease engaging in appropriate behavior because controlling contingencies are predictably not in effect (Corte, Wolf, & Locke, 1971;Marholin & Steinman, 1977;Risley, 1968). Thus, autistic children may be especially likely to display off-task responding when a teacher or therapist's departure indicates that no contingencies will be applied for a period of time.…”
mentioning
confidence: 99%